Dimensões formativas da prática da escrita na formação inicial - Torrezan, Hayla Emanuelle [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research focuses on the practice of writing in the initial formation of teachers. My interest for this thematic arose from my participation in the extension project Formation Group: Dialog and Otherness and the extension course School: local for teacher formation, both coordinated by my supervisor. After all, I had the possibility of experimenting the exercise of writing and acknowledging the relevance of it in these contexts, in my condition of teacher-in-training. This thematic has involved me, which is why I conducted an autobiographical investigation. As data gathering tools, I used papers that I produced, as participant of the aforementioned extension project and extension course. Those papers were file records I made from the meetings, monthly papers produced from a thematic that was chosen by the graduating students that attended the extension project and, furthermore, I bring a self-assessments I developed inspired by the experiences I had in these two formative gaps. All these experiences provided pieces of my formative experience as a future teacher. The research aimed to understand which act of writing mobilized knowledge and triggered reflections in the aforementioned contexts, based on paper analysis, seeking to legitimate the importance of this practice in my formative process. Furthermore, a bibliographical research of qualitative nature was developed, achieved from the statement and analysis of articles located in the Annals of International Congress of (Auto) Biography Research (CIPA, in Portuguese acronym), from 2006 to 2012, and in the Annals of National Conference of Didactic and Teaching Techniques (ENDIPE, in Portuguese acronym), in the period from 2006 to 2012. This bibliographical research aimed to increase the understanding of the formative dimension of the practice of writing in the initial training in Pedagogy. I sought to distinguish the writing practices promoted in the context of initial...

A pesquisa possui como foco a prática da escrita na formação inicial de professores. O interesse pela temática surgiu a partir da minha participação no projeto de extensão Grupo de Formação: Diálogo e Alteridade e no curso de extensão Escola: espaço de formação de professores, ambos coordenados por minha orientadora. Isto porque foram nestes contextos que tive a possibilidade de vivenciar o exercício da escrita e perceber a importância da mesma em minha constituição como professora em formação. Esta temática tem me envolvido, motivo pelo qual foi realizada uma pesquisa autobiográfica, utilizando como instrumentos de coleta de dados escritas produzidas por mim como participante do referido projeto de extensão e do curso de extensão. Essas escritas são: registros que fiz dos encontros, escritas mensais produzidas a partir de uma temática escolhida pelos graduandos que participavam do projeto de extensão e, além disso, trago uma escrita que elaborei inspirada nas vivências que tive nesses dois espaços formativos, sendo que todas elas trazem fragmentos da minha experiência formativa enquanto futura professora. A pesquisa objetivou, a partir da análise das escritas, compreender quais saberes foram mobilizados e quais reflexões puderam ser desencadeadas a partir do ato da escrita nos referidos contextos, procurando legitimar a importância desta prática em meu processo formativo. Somado a isto, foi desenvolvida uma pesquisa bibliográfica de natureza qualitativa, realizada a partir do levantamento e análise de artigos localizados nos Anais do Congresso Internacional de Pesquisa (Auto)Biográfica (CIPA), no período de 2006-2012, e nos Anais do Encontro Nacional de Didática e Práticas de Ensino (ENDIPE), no período de 2006-2012, na busca por ampliar a compreensão da dimensão formativa da prática da escrita no âmbito da formação inicial (Pedagogia). Busco distinguir quais as práticas de escrita...
Keywords: Professores - Formação; Pratica de ensino; Escrita; Pesquisa bibliografica